2017
DOI: 10.1177/0001699317710704
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in protest activities between natives and individuals of migrant origin in Europe

Abstract: This article explores gaps in protest engagement between natives and individuals of migrant origin in European cities. It examines migrant-native gaps and second generation-native gaps by associating them with different sources of inequalities: differential individual SES resources, differential attitudes, and differential characteristics related to migration; differential effects of such factors for natives and for individuals of migrant origin; and differential contexts offering varying opportunities of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…To answer these questions, we integrate insights from the literature on political transnationalism, a concept identifying situations in which migrants find themselves embedded and acting in and between two countries, the countries of origin and the countries of residence (Schiller et al 1995;Vertovec 2004;Mouw et al 2014), with the insights derived from the literature on migrants' political integration in the countries of residence (Koopmans et al 2005;de Rooij 2012;Just and Anderson 2014;Pilati 2018). Our first contribution is to reinforce studies trying to combine perspectives on transnational practices with those on migrants' political integration in the residence countries (Ahmadov and Sasse 2016;Mügge 2016, p. 110; for similar studies in relation to the economic dimension, specifically remittances, cf.…”
Section: Introductionmentioning
confidence: 99%
“…To answer these questions, we integrate insights from the literature on political transnationalism, a concept identifying situations in which migrants find themselves embedded and acting in and between two countries, the countries of origin and the countries of residence (Schiller et al 1995;Vertovec 2004;Mouw et al 2014), with the insights derived from the literature on migrants' political integration in the countries of residence (Koopmans et al 2005;de Rooij 2012;Just and Anderson 2014;Pilati 2018). Our first contribution is to reinforce studies trying to combine perspectives on transnational practices with those on migrants' political integration in the residence countries (Ahmadov and Sasse 2016;Mügge 2016, p. 110; for similar studies in relation to the economic dimension, specifically remittances, cf.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that my study captures something different than perceptions of discrimination, frequently studied in previous work (Waisman 2008;Heath and Demireva 2014;Pilati 2018). Exposure to contextual hostility is another form of personal experience, including discrimination but also covering more indirect expressions of hostility.…”
Section: Resultsmentioning
confidence: 96%
“…An example of a direct form of hostile expression is outspoken racism specifically aimed towards the individual, whereas indirect expressions of hostility include negative statements about immigration or immigrants as a group in general. Discrimination is also a specific form of hostile expressions, often the main focus in previous studies (Waisman 2008;Heath and Demireva 2014;Pilati 2018). Exposure to contextual hostility is thus a broader set of experiences that includes but is not exclusive to perceptions of discrimination.…”
Section: Introductionmentioning
confidence: 95%
“…They have all managed to build wide and strong networks, in Finland and abroad. Level of education is also important here and might help to explain their political participation (see also Pilati 2017;Ronkainen 2009). All of the participants have post-compulsory education and are currently either studying or preparing for entry exams or else are in work.…”
Section: Emotional Capital Converges With Cultural and Social Forms Omentioning
confidence: 99%
“…Past research on young migrants' political and civic involvement based on survey data and quantitative methods indicate that there is often no gap between second-generation migrants' and young natives' political participation at the general level (Heath et al 2013;Pilati 2017;Quintelier 2009). Some studies that look at both civic and formal political involvement of young people with survey data in the European context have shown that, at times, young people of migrant origin are even more active than their native peers (Kim & Amnå 2015;Noack & Jugert 2015).…”
Section: Introductionmentioning
confidence: 99%